2000
DOI: 10.1128/mcb.20.17.6579-6586.2000
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Regulation of Cdx1: an Indirect Mechanism for Retinoids and Vertebral Specification

Abstract: Retinoic acid (RA) is required for diverse developmental programs, including vertebral specification. Both RA receptor disruption and excess RA result in homeotic transformations of the axial skeleton. These effects are believed to occur through altered expression of Hox genes, several of which have been demonstrated to be direct RA targets. Members of the cdx (caudal) homeobox gene family are also implicated in regulating Hox expression. Disruption of cdx1 results in vertebral homeotic transformations and alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 46 publications
6
103
0
1
Order By: Relevance
“…Activation of this regulatory module by the onset of gastrulation requires the activation and up-regulation of the Cdx genes. Multiple signals have been identified that contribute to Cdx expression including FGF, Wnt, BMP, and retinoic acid (Pillemer et al, 1998b;Houle et al, 2000;Keenan et al, 2006;Pilon et al, 2006). The surprising finding was that, initially, during late blastula, the Oct3/4 factors promote Cdx1 expression through up-regulation of FGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of this regulatory module by the onset of gastrulation requires the activation and up-regulation of the Cdx genes. Multiple signals have been identified that contribute to Cdx expression including FGF, Wnt, BMP, and retinoic acid (Pillemer et al, 1998b;Houle et al, 2000;Keenan et al, 2006;Pilon et al, 2006). The surprising finding was that, initially, during late blastula, the Oct3/4 factors promote Cdx1 expression through up-regulation of FGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse Cdx1 is activated by retinoic acid (RA) in both embryos (Houle et al, 2000) and P19 or F9 embryonal carcinoma cells (Beland and Lohnes, 2005;Houle et al, 2000). RA response reporter studies show that RA is present in the embryonic regions known to express Cdx1: the primitive streak of 7.5 day mouse embryos and, by 8.5 days, the developing somites (Rossant et al, 1991).…”
Section: Abstract: Cdx1 Retinoic Acid Response Element Evolutionmentioning
confidence: 99%
“…The Cdx1 upstream RARE (Houle et al, 2000) is atypical in containing only one clear consensus element.…”
Section: [G][a][c/a][c][t/c]mentioning
confidence: 99%
See 2 more Smart Citations